A self-consistent method to determine accessible volume, area and pore size distribution (APSD) of BPL, Norit and AX-21 activated carbon - Herrera, L.; Fan, Chunyan; Nguyen, V.; Do, D.; Horikawa, T.; Nicholson, D. (Pergamon, 2012)
Accessible volume, geometrical area and accessible pore size distribution are the fundamental structural parameters in the characterization of porous solids. We provide a novel "inverse" procedure, which is based on the mass balance and an MC optimization scheme, to determine these parameters from the analysis of experimental adsorption isotherms for a number of commonly used activated carbons: BPL, AX-21 and Norit. Our results, based on a kernel of model pores generated from GCMC simulations, are compared with, and shown to be different from, the results obtained from the conventional method. We show that the discrepancies arise from an incorrect evaluation of both micropore and mesopore sizes. © 2011 Elsevier Ltd. All rights reserved.